Osvrt na djelatnost osposobljavanja osoba za vozače vozila na motorni pogon - Smoljan, Ivan (Promet - Traffic&Transportation, 2012)
Over the last four years in the Republic of Croatia changes have taken place also in the segment of motorists training and licensing in an atmosphere of significant social, political and economic changes and wartime conditions. Regulations have undergone change in this segment insomuch that it has been structured on a marketing basis, training has been separated from licensing examinations, while the number of Driving Schools has tippled, and the segment has been given the required competitive atmosphere. From the aspect of training/licensing programs and management the segment has almost reached the level of same aspects in individual European countries. It is necessary to pass as soon as possible respective regulations for this segment coordinated with the new Road Traffic Safety Act and to structure the segment of motorists training and licensing in conformance with these regulations.